Recurrent penile squamous cell carcinoma in an elderly circumcised man. (20th February 2017) - Kravvas, G.; Veitch, D.; Doiron, P. R.; Freeman, A.; Muneer, A.; Dinneen, M.; Francis, N.; Bunker, C. B.
Abstract : Clickhere for the corresponding questions to this CME article.